2015
DOI: 10.1037/a0039176
|View full text |Cite
|
Sign up to set email alerts
|

Children draw more affiliative pictures following priming with third-party ostracism.

Abstract: Humans have a strong need to belong. Thus, when signs of ostracism are detected, adults often feel motivated to affiliate with others in order to reestablish their social connections. This study investigated the importance of affiliation to young children following priming with ostracism. Four-and 5-year-old children were primed with either ostracism or control videos and their understanding of, and responses to, the videos were measured. Results showed that children were able to report that there was exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 55 publications
9
77
0
Order By: Relevance
“…This result has recently been replicated and extended by Watson-Jones and colleagues who have shown that children imitate more closely on a number of tasks following videos depicting exclusion than following videos depicting inclusion [102]. Further research using this basic paradigm has shown that children also draw pictures that depict more affiliative relationships following priming with exclusion [103].…”
Section: (D) Consequences Of Social Exclusionsupporting
confidence: 66%
“…This result has recently been replicated and extended by Watson-Jones and colleagues who have shown that children imitate more closely on a number of tasks following videos depicting exclusion than following videos depicting inclusion [102]. Further research using this basic paradigm has shown that children also draw pictures that depict more affiliative relationships following priming with exclusion [103].…”
Section: (D) Consequences Of Social Exclusionsupporting
confidence: 66%
“…A further possible future direction is motivated by Song et al. 's () study in which they showed that children's drawings became more affiliative when they were primed with observed third‐party ostracism videos. In our study, the order of the assessment for eye‐tracking and SSP was fixed and we think it is unlikely that the prior viewing of animations could have had a major impact on the classification of the infants as secure or insecure.…”
Section: Discussionmentioning
confidence: 99%
“…One well‐known behavioral response to exclusion is pro‐sociality and conformism. Various studies have shown that also children as young as 4 years of age engage in affiliative and imitative behavior after being primed with vicarious exclusion (i.e., Song, Over, & Carpenter, ; Watson‐Jones, Legare, Whitehouse, & Clegg, ). In effect, the primary function of exclusion is social control.…”
Section: The Negative Consequences Of Social Exclusion In the Developmentioning
confidence: 99%